NILAI PENDIDIKAN DALAM TRADISI TURUN MANDI DI SUNGAI DAREH KABUPATEN SOLOK PROVINSI SUMATERA BARAT - Saputra, Indrian; Al-Firdaus; Rinaldi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This research is qualitative research. Data sources used include interviews, observation and documentation. The aim of this research is to understand the meaning of the bathing tradition, the process of carrying out the bathing event, and the values ​​of Islamic education contained in this tradition in Jorong Sungai Dareh. The research results show that the tradition of bathing is the first moment for children to be introduced to the surrounding environment. Apart from that, this tradition is also a form of gratitude for the birth of a child. The implementation of the bathing tradition is carried out in several stages, including determining the day, mammanggia, cooking together (mamasak basamo), baarak bako, baarak bathing the child, the process of bathing the child, mamabadak, and praying together. The educational values ​​contained in the bathing tradition include gratitude, friendship, worship, mutual cooperation, almsgiving, respect for guests, and caring.